2001
DOI: 10.1074/jbc.m009024200
|View full text |Cite
|
Sign up to set email alerts
|

A Regulatory Hydrophobic Area in the Flexible Joint Region of Plasminogen Activator Inhibitor-1, Defined with Fluorescent Activity-neutralizing Ligands

Abstract: We have characterized the neutralization of the inhibitory activity of the serpin plasminogen activator inhibitor-1 (PAI-1) by a number of structurally distinct organochemicals, including compounds with environmentsensitive spectroscopic properties. In contrast to latent and reactive center-cleaved PAI-1 and PAI-1 in complex with urokinase-type plasminogen activator (uPA), active PAI-1 strongly increased the fluorescence of the PAI-1-neutralizing compounds 1-anilinonaphthalene-8-sulfonic acid and 4,4-dianilino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
104
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(113 citation statements)
references
References 65 publications
8
104
1
Order By: Relevance
“…The second site was consistent with a previously described organochemical compound binding site, bordered by β-strand 1A, strand 2A, and α-helix D (sA/hD pocket; Fig. S2) (9). However, as discussed below, biochemical and mutational analyses of these two regions revealed that the sB/sC pocket site most likely represented the high-affinity functional binding site for CDE-096 and suggested that the sA/hD pocket interaction was likely a result of the high concentrations of CDE-096 used for crystal soaking studies.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…The second site was consistent with a previously described organochemical compound binding site, bordered by β-strand 1A, strand 2A, and α-helix D (sA/hD pocket; Fig. S2) (9). However, as discussed below, biochemical and mutational analyses of these two regions revealed that the sB/sC pocket site most likely represented the high-affinity functional binding site for CDE-096 and suggested that the sA/hD pocket interaction was likely a result of the high concentrations of CDE-096 used for crystal soaking studies.…”
Section: Resultssupporting
confidence: 58%
“…These associations have made PAI-1 an attractive pharmaceutical target. However, despite extensive studies, only a few small molecule inhibitors have been identified thus far (7)(8)(9)(10)(11)(12)(13)(14)(15)(16), and the majority of these are poor pharmaceutical candidates as they have relatively low affinity for PAI-1 and are unable to inactivate PAI-1 bound to its plasma cofactor vitronectin.…”
mentioning
confidence: 99%
“…Several other small molecules have been determined to bind in the same, or similar, region of PAI-1, e.g. ANS, bis-ANS, and XR5118 (51). Among the small molecule inhibitors, AZ3976 is unique because it (a) binds preferentially to latent PAI-1 over active PAI-1 and (b) inhibits PAI-1 by accelerating latency transition.…”
Section: Discussionmentioning
confidence: 99%
“…This part of PAI-1 includes what is referred to as the flexible joint region (i.e. ␣-hD, ␣-hF, and ␤-s1A) because it participates in structural rearrangements going from active PAI-1 to the irreversible PAI1⅐tPA complex (51). The presence of five hydrogen bonds indicates specific interactions between PAI-1 and AZ3976.…”
Section: Discussionmentioning
confidence: 99%
“…The flexible structure of PAI-1, the lack of a rigid active site, and its multiple functions all contribute to the difficulties in identifying and designing small-molecule PAI-1 inactivators. Despite these obstacles, several small-molecule PAI-1 inhibitors have been described (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36); however, each has significant limitations that have reduced their potential for further drug development.…”
mentioning
confidence: 99%